Evaluation of Innotrac Aio! Second-Generation Cardiac Troponin I Assay: The Main Characteristics for Routine Clinical Use. (2006) - Hedberg, P.; Valkama, J.; Suvanto, E.; Pikkujämsä, S.; Ylitalo, K.; Alasaarela, E.; Puukka, M.
Abstract : The availability of a simple, sensitive, and rapid test using whole blood to facilitate processing and to reduce the turnaround time could improve the management of patients presenting with chest pain. The aim of this study was an evaluation of the Innotrac Aio! second-generation cardiac troponin I (cTnI) assay. The Innotrac Aio! second-generation cTnI assay was compared with the Abbott AxSYM first-generation cTnI, Beckman Access AccuTnI, and Innotrac Aio! first-generation cTnI assays. We studied serum samples from 15 patients with positive rheumatoid factor but with no indication of myocardial infarction (MI). Additionally, the stability of the sample with different matrices and the influence of hemodialysis on the cTnI concentration were evaluated. Within-assay CVs were 3.2%–10.9%, and between-assay precision ranged from 4.0% to 17.2% for cTnI. The functional sensitivity ( CV = 20 % ) and the concentration giving CV of 10% were approximated to be 0.02 and 0.04, respectively. The assay was found to be linear within the tested range of 0.063–111.6 μ g/L. The correlations between the second-generation Innotrac Aio!, Access, and AxSYM cTnI assays were good (r coefficients 0.947–0.966), but involved differences in the measured concentrations, and the biases were highest with cTnI at low concentrations. The second-generation Innotrac Aio! cTnI assay was found to be superior to the first-generation assay with regard to precision in the low concentration range. The stability of the cTnI level was best in the serum, lithium-heparin plasma, and lithium-heparin whole blood samples (n = 10, decrease < 10 % in 24 hours at + 20 ° C and at + 4 ° C . There was no remarkable influence of hemodialysis on the cTnI release. False-positive cTnI values occurred in the presence of very high rheumatoid factor values, that is, over 3000 U/L. The 99th percentile of the apparently healthy reference group was ≤ 0.03   μ g/L . The results demonstrate the very good analytical performance of the second-generation Innotrac Aio! cTnI assay.